Growth and differentiation of human induced pluripotent stem cell (hiPSC)-derived kidney organoids using fully synthetic peptide hydrogels - Niall J. Treacy; Shane Clerkin; Jessica L. Davis; Ciarán Kennedy; Aline F. Miller; Alberto Saiani; Jacek K. Wychowaniec; Dermot F. Brougham; John Crean (Bioactive Materials, 2023)
Human induced pluripotent stem cell (hiPSC)-derived kidney organoids have prospective applications ranging from basic disease modelling to personalised medicine. However, there remains a necessity to refine the biophysical and biochemical parameters that govern kidney organoid formation. Differentiation within fully-controllable and physiologically relevant 3D growth environments will be critical to improving organoid reproducibility and maturation. Here, we matured hiPSC-derived kidney organoids within fully synthetic self-assembling peptide hydrogels (SAPHs) of variable stiffness (storage modulus, G′). The resulting organoids contained complex structures comparable to those differentiated within the animal-derived matrix, Matrigel. Single-cell RNA sequencing (scRNA-seq) was then used to compare organoids matured within SAPHs to those grown within Matrigel or at the air-liquid interface. A total of 13,179 cells were analysed, revealing 14 distinct clusters. Organoid compositional analysis revealed a larger proportion of nephron cell types within Transwell-derived organoids, while SAPH-derived organoids were enriched for stromal-associated cell populations. Notably, differentiation within a higher G’ SAPH generated podocytes with more mature gene expression profiles. Additionally, maturation within a 3D microenvironment significantly reduced the derivation of off-target cell types, which are a known limitation of current kidney organoid protocols. This work demonstrates the utility of synthetic peptide-based hydrogels with a defined stiffness, as a minimally complex microenvironment for the selected differentiation of kidney organoids.